2018
DOI: 10.1177/1066896918796946
|View full text |Cite
|
Sign up to set email alerts
|

Cribriform-Morular Variant of Papillary Thyroid Carcinoma With Poorly Differentiated Features: A Case Report With Immunohistochemical and Molecular Genetic Analysis

Abstract: Cribriform-morular variant of papillary thyroid carcinoma (CMVPTC) is usually an inherited malignancy and may be a presenting indicator of familial adenomatous polyposis syndrome although it may occasionally be sporadic. Known CMVPTC mutations include adenomatous polyposis coli ( APC) and β-catenin ( CTNNB1) genes. Despite its malignant classification, CMVPTC is considered to be a well-differentiated thyroid tumor with a generally good behavior. In contrast, poorly differentiated thyroid carcinoma is an aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…[ 146 ]. This is also depicted in our review, where few patients went disease-free [ 36 , 39 , 45 , 52 , 53 , 54 , 56 , 58 , 59 , 64 , 65 , 68 , 71 , 72 , 87 , 96 , 99 , 103 , 104 , 106 , 108 , 117 , 118 ]. Distant metastases represent the most significant cause of death in PDTC, with the majority of patients succumbing to the disease.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…[ 146 ]. This is also depicted in our review, where few patients went disease-free [ 36 , 39 , 45 , 52 , 53 , 54 , 56 , 58 , 59 , 64 , 65 , 68 , 71 , 72 , 87 , 96 , 99 , 103 , 104 , 106 , 108 , 117 , 118 ]. Distant metastases represent the most significant cause of death in PDTC, with the majority of patients succumbing to the disease.…”
Section: Discussionsupporting
confidence: 78%
“…Since cytological diagnosis of PDTC based on FNAC is challenging, our review has shown that some patients underwent a hemithyroidectomy or subtotal thyroidectomy with a completion thyroidectomy after histological diagnosis [ 38 , 44 , 52 , 54 , 59 , 65 , 69 , 85 , 103 , 104 , 107 , 108 , 115 , 117 ], but the majority of them were submitted to a total thyroidectomy as the initial operation [ 40 , 41 , 42 , 43 , 46 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 56 , 58 , 60 , 61 , 62 , 64 , 67 , 68 , 69 , 72 , 73 , 75 , 79 , 80 , 81 , 82 , 85 , 86 , 88 , 89 , 90 , 91 , 92 , 93 , 95 , 96 , 100 , 101 ,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cribriform-morular thyroid carcinoma is a rare cancer that can present as an extracolonic manifestation of FAP syndrome. Case reports of cribriform-morular thyroid carcinoma typically have demonstrated evidence of thyroid nodules or a thyroid mass on ultrasound imaging ( 4‐7 ). A retrospective review of ultrasonographic and clinical characteristics of 5 patients with cribriform-morular variant thyroid carcinoma showed that all had either palpable discrete lesions or nodules on ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…According to the criteria of the new edition of the WHO classification of thyroid tumors ( 1 , 6 ), rare cases of ‘high-grade CMTC’ with necrosis and/or high proliferative activity have also been reported ( 7 , 9 , 46 , 50 – 52 ).…”
Section: Pathological Featuresmentioning
confidence: 99%